Virtual tools in distance education: university satisfaction regarding its application as part of teaching strategies - Guillermo Morales-Romero; José Antonio Arévalo-Tuesta; Lilia Rodas-Camacho; Elizabeth Auqui-Ramos; Carlos Palacios-Huaraca; César Trujillo-Hinojosa; Elvira Caceres-Cayllahua (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
When virtual education was implemented in Peru, the limitations of teachers in technological management were evident. For this reason, the research seeks to analyze the perception of university satisfaction regarding the use of virtual teacher tools as part of teaching strategies, in order to improve virtual teaching-learning, achieving student motivation and facilitating this meaningful learning through the use of virtual tools. The method used according to the investigative approach is qualitative, according to its scope it is descriptive and correlational. During the development of the research, it was identified that the satisfaction regarding the use of virtual tools by the teacher is focused on the critical, constructive and positive attitude towards virtual tools and in the acquittal of students' questions regarding the use of virtual tools. On the other hand, the indicator that is related to low student satisfaction focuses on the low diversity of methodological strategies used for the development of virtual learning sessions. Likewise, the Chi-square test shows the significant relationship between the perception of the teacher's competences regarding the use of virtual tools and the perception of the quality of the teaching offered to students during distance education.